A Comprehensive Process Of Nitrogen Fixation In Plants - Amar Ma’ruf; Syahminar Syahminar; Cik Zulia (Agrium, 2023)
Nitrogen is a component of several biomolecules that are essential for all organisms' growth and development. Nitrogen fixation is the biological process that converts molecular nitrogen to ammonia. Biological nitrogen fixation is mediated by diazotroph microorganisms that use nitrogenase enzymes to enhance atmospheric nitrogen. Much of this is accomplished through a symbiotic interaction between plants and diazotrophic bacteria. Microbiology and plant biology are discussed in symbiotic nitrogen fixation discussions. Some of the nitrogen fixation mechanisms mentioned in this paper begin with the formation of nodules, the action of the nitrogenase enzyme in reducing nitrogen to ammonia, and the presence of rhizobia in nodules. This study provides a comprehensive overview of the nodule formation process, the role of the nitrogenase enzyme in reducing nitrogen to ammonia, and the presence of rhizobia in nodules. A more complete literature review on biological nitrogen fixing in plants is required to obtain more specific information.